Splenic inflammatory pseudotumor-like follicular dendritic cell sarcoma: a case report with imaging features and literature review - Shang, Ruimiao; Zhu, Shuxu; Tao, Xiaoying (Frontiers in Oncology, 2026)
BackgroundFollicular dendritic cell sarcoma (FDCS) is an extremely rare malignant neoplasm originating from immune follicular dendritic cells. Its inflammatory pseudotumor-like subtype (IPT-like FDCS) is even more uncommon due to morphological overlap with inflammatory pseudotumors. We report a case of splenic IPT-like FDCS and perform a systematic literature review to clarify the multimodal imaging characteristics of this rare entity.Case presentationA 50-year-old asymptomatic man had an incidentally detected splenic mass during routine health screening. Ultrasound showed a well-defined hypoechoic splenic lesion. Magnetic resonance imaging revealed slightly hyperintense signals on both T1- and T2-weighted images, with progressive inhomogeneous enhancement and a peripheral hypointense ring on T2-weighted sequences. The patient underwent splenectomy, and IPT-like FDCS was confirmed via histopathology and immunohistochemistry.ConclusionsSplenic IPT-like FDCS typically presents with nonspecific or subclinical manifestations, making noninvasive imaging modalities crucial for diagnostic hint. Progressive heterogeneous enhancement and a peripheral hypointense ring on T2-weighted imaging may be valuable imaging features for identifying this rare malignancy.